Detection of Enterotoxigenic Clostridium perfringens Type A Isolates in American Retail Foods - Wen, Qiyi (American Society for Microbiology, 2004)
Currently there is only limited understanding of the reservoirs for Clostridium perfringens type A food poisoning. A recent survey (Y.-T. Lin and R. Labbe, Appl. Environ. Microbiol. 69:1642-1646, 2003) of non-outbreak American retail foods did not identify the presence of a single C. perfringens isolate carrying the enterotoxin gene (cpe) necessary for causing food poisoning. The present study revisited this issue, using revised methodology and food sampling strategies. In our survey, cpe-positive C. perfringens isolates were detected in ∼1.4% of ∼900 surveyed non-outbreak American retail foods. Interestingly, those enterotoxigenic isolates in non-outbreak foods appear indistinguishable from C. perfringens isolates known to cause food poisoning outbreaks: i.e., the enterotoxigenic retail food isolates all carry a chromosomal cpe gene, are classified as type A, and exhibit exceptional heat resistance. Collectively, these findings indicate that some American foods are contaminated, at the time of retail purchase, with C. perfringens isolates having full potential to cause food poisoning. Furthermore, demonstrating that type A isolates carrying a chromosomal cpe gene are the enterotoxigenic isolates most commonly present in foods helps to explain why these isolates (rather than type A isolates carrying a plasmid cpe gene or cpe-positive type C or D isolates) are strongly associated with food poisoning outbreaks. Finally, since type A chromosomal cpe isolates present in the surveyed raw foods exhibited strong heat resistance, it appears that exceptional heat resistance is not a survivor trait selected for by cooking but is instead an intrinsic trait possessed by many type A chromosomal cpe isolates.